Approximation of general zero-range potentials - Albeverio, S.; Nizhnik, L.P. (Український математичний журнал, 2000)
A norm resolvent convergence result is proved for approximations of general Schrodinger operators with zero-range potentials. An approximation of the δ’-interaction by nonlocal non-Hermitian potentials (without a renormalization of the coupling constant) is also constructed. Наведено результати про апроксимацію загальних операторів Шредінгера з потенціалом нульового радіуса в сенсі резольвентно! збіжності за нормою. Побудовано апроксимацію δ’-взаємодії за допомогою нелокальних неермітових потенціалів (без перенормування константи взаємодії).